Sustainable Retrofitting of Existing Buildings: Techniques and Case Studies - Ojong Felix Enow; Ebimor Yinka Gbabo; Andrew Tochukwu Ofoedu; Possible Emeka Chima; Oluwapelumi Joseph Adebowale (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Retrofitting existing buildings for sustainability has become a critical endeavor in the quest for more energy-efficient and environmentally friendly built environments. This abstract explores the techniques and case studies associated with sustainable retrofitting, highlighting the challenges, benefits, and best practices in this field. The sustainable retrofitting of existing buildings involves the application of innovative technologies and strategies to improve energy efficiency, reduce environmental impact, and enhance occupant comfort. Techniques such as improved insulation, energy-efficient lighting, and HVAC system upgrades are commonly employed to achieve these goals. Additionally, the integration of renewable energy sources, such as solar panels and wind turbines, can further enhance the sustainability of retrofitted buildings. Several case studies illustrate the successful implementation of sustainable retrofitting techniques. For example, the Empire State Building in New York City underwent a comprehensive retrofitting project that resulted in a 38% reduction in energy consumption and a 105,000 metric ton reduction in greenhouse gas emissions annually. Similarly, the Bullitt Center in Seattle, Washington, is a net-zero energy building that was retrofitted to achieve high levels of energy efficiency and environmental sustainability. Challenges associated with sustainable retrofitting include high initial costs, technical complexities, and the need for skilled labor. However, the long-term benefits, such as reduced energy bills, increased property value, and a smaller environmental footprint, outweigh these challenges. Best practices for sustainable retrofitting include conducting a thorough energy audit, engaging with stakeholders, and selecting cost-effective and environmentally friendly technologies. In conclusion, sustainable retrofitting of existing buildings is a key strategy for achieving energy efficiency and environmental sustainability in the built environment. By employing innovative techniques and drawing on successful case studies, stakeholders can overcome challenges and reap the benefits of sustainable retrofitting.
Keywords: Sustainable; Retrofitting; Existing Buildings; Techniques; Case Studies